PPP and the Balassa Samuelson Effect : The Role of the Distribution Sector - MacDonald, Ronald (IMF Working Papers; Working Paper ;, 2001)
This paper investigates the impact of the distribution sector on the real exchange rate, controlling for the Balassa-Samuelson effect, as well as other macro variables. Long-run coefficients are estimated using a panel dynamic OLS estimator. The main result is that an increase in the productivity and competitiveness of the distribution sector with respect to foreign countries leads to an appreciation of the real exchange rate, similarly to what a relative increase in the domestic productivity of tradables does. This contrasts with the result that one would expect by considering the distribution sector as belonging to the non-tradable sector. One explanation may lie in the use of the services from the distribution sector in the tradable sector. Our results also contribute to explaining the so-called PPP puzzle.